Ecclesiastical biography, or, Lives of eminent men connected with the history of religion in England: from the commencement of the Reformation to the Revolution - Wordsworth, Christopher (Printed for F. C. and J. Rivington, No. 62, St. Paul's Church-yard, 1810)
v. 1. John Wickliffe. William Thorpe. Lord Cobham. Invention of printing. Progress of reformation. Colet, Chaucer, Luther. Cardinal Wolsey.--v. 2. Thomas Bilney. Thomas More. William Tindall. Cromwell, earl of Essex. John Rogers. Bishop Hooper. Rowland Taylor.--v. 3. Bishop Latimer. Bish op Ridley. Archbishop Cranmer.--v. 4. Bishop Jewel. Bernard Gilpin. Richard Hooker. Archbishop Whitgift. John Donne. George Herbert.--v. 5. Henry Wotton. Nicholas Ferrar. Bishop Hall. Henry Hammond. Bishop Sanderson. Richard Baxter.--v. 6. Matthew Hale. Philip Henry. Earl of Rochester. Archbishop Tillotson. Index.